Systemic Besnoitiosis in a Juvenile Roe Deer (Capreolus capreolus). Issue 5 (26th May 2016) - Arnal, M. C.; Gutiérrez‐Expósito, D.; Martínez‐Durán, D.; Regidor‐Cerrillo, J.; Revilla, M.; Fernández de Luco, D.; Jiménez‐Meléndez, A.; Ortega‐Mora, L. M.; Álvarez‐García, G.
Summary: Herein, we report the first incidence of systemic besnoitiosis in a male juvenile roe deer Capreolus capreolus . The animal was found dead in an area where bovine besnoitiosis is endemic and showed cachexia and multiple skin erosions in the metacarpal and metatarsal areas. Moreover, round and elevated white structures suggestive of Besnoitia spp. tissue cysts were also present. Twenty‐eight tissue samples from different anatomical locations were collected for microscopic lesion and parasite detection through histopathology and PCR. Immunohistochemistry was performed to confirm Besnoitia ‐positive reaction in the tissue cysts. In addition, the identity of Besnoitia spp. in PCR‐positive tissue samples was also investigated using microsatellite (MS) markers, and the comparison of protein disulphide isomerase gene sequences (Bb PDI ) of B. besnoiti and B. tarandi isolated from cattle and reindeer, respectively. Besnoitia cysts were detected in the skin (several parts), respiratory and upper digestive tracts, eyes, kidney, liver, testicle, cardiac muscle and lymphoid tissue. Remarkably, the presence of tissue cysts in the brain confirmed the capacity of Besnoitia spp. to form tissue cysts in the central nervous system (CNS). Finally, the Besnoitia species detected showed the same MS genotype as B. besnoiti, and Bb PDI sequences from roe deer and two B. besnoiti isolates were genetically identical throughout multiple sequence alignment. Thus, for the first time, there is evidence that roe deer might act as an intermediate host of B. besnoiti . Further molecular analyses and parasite isolations are needed to corroborate these findings.